PROBLEMS REGARDING THE AWARDING OF BENEFIT DERIVED FROM UNLAWFUL USE OF A TRADE SECRET TO THE INJURED PERSON - Kontrimas, Vaidas (Teisė, 2017)
This article provides an analysis of the legal basis (using the institute of civil liability or unjust enrichment) for awarding the benefit of the infringer, derived from unfair competition actions upon unlawful disclosure and use of the other entity’s trade secret, to the injured person. The article also deals with the new judicial interpretations in relation to civil liability for unfair competition actions related to awarding of loss of the injured person’s profit and the infringer’s benefit (including the correlation between them), developed by the Supreme Court of Lithuania. The article assesses legal justification for such judicial interpretations and possible negative consequences of their application.